Effects of sulfur-containing antioxidants on malondialdehyde and catalase levels of liver, kidney and brain in lead-exposed rats - Çaylak, Emrah; Halifeo?lu, Ihsan (Turkiye Klinikleri, 2007)
Objective: Lead causes a great environmental problem because it is widely used in the industry. Several studies focusing on its effects on human and animals were carried out. Sulphur containing antioxidants were observed to have beneficial effects against lead's detrimental properties in experimental studies. The aim of our study was to evaluate the antioxidant effects of some sulphur-containing compounds in rats where oxidative stress was induced by lead acetate. Material and Methods: Oxidative stress parameters were determined (Hb in whole blood, MDA and CAT in liver, kidney and brain) in rats following the administration of lead and sulphur containing antioxidants [L-methionine, lipoic acid (LA), N-acetylcysteine (NAC), L-homocysteine (L-Hcy)]. Results: In the lead group Hb levels were determined to be significantly low (p< 0.01) whereas MDA levels were higher compared to controls. Hb levels in lead-methionine and lead-LA groups were significantly lower compared to lead group (p< 0.05). MDA levels of lead-NAC group were reduced in all tissues compared to lead group whereas there was an increase over control values in liver CAT activities (p< 0.05) in lead-LA group. Kidney CAT activities were significantly low in lead-NAC (p< 0.05), and lead-Hcy (p< 0.01) groups compared to lead group. Conclusion: It is believed that oxidative stress induced by lead is reduced by sulphur-containing compounds. Copyright © 2007 by Türkiye Klinikleri.
Sülfür i?çeren antioksidanlarin kurşuna maruz kalmiş ratlarda karaci?er, böbrek ve beyin malondialdehit ve katalaz düzeylerine antioksidan etkileri
Keywords: Acetylcysteine; Homocysteine; Lead; Methionine; Thioctic acid